2021
DOI: 10.3390/biology10121301
|View full text |Cite
|
Sign up to set email alerts
|

Immunoautophagy-Related Long Noncoding RNA (IAR-lncRNA) Signature Predicts Survival in Hepatocellular Carcinoma

Abstract: Background: The dysregulation of autophagy and immunological processes has been linked to various pathophysiological conditions, including cancer. Most notably, their particular involvement in hepatocellular carcinoma (HCC) is becoming increasingly evident. This has led to the possibility of developing a prognostic signature based on immuno-autophagy-related (IAR) genes. Given that long non-coding RNAs (lncRNAs) also play a special role in HCC, a combined signature utilizing IAR genes and HCC-associated long n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…To further evaluate the FRlncRNA signature, we compared our risk model with reported risk models based on immune- or ferroptosis-related lncRNAs to predict prognosis of HCC. The formulae to calculate risk scores were retrieved from the publications and recalculated in our dataset [ 34 36 ]. Our signature showed better prediction ability (AUC = 0.779) compared to other three models (AUC = 0.729, 0.750 and 0.764) (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the FRlncRNA signature, we compared our risk model with reported risk models based on immune- or ferroptosis-related lncRNAs to predict prognosis of HCC. The formulae to calculate risk scores were retrieved from the publications and recalculated in our dataset [ 34 36 ]. Our signature showed better prediction ability (AUC = 0.779) compared to other three models (AUC = 0.729, 0.750 and 0.764) (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ji et al ( 21 ) showed that LINC00152 could activate the mammalian target of rapamycin (mTOR) signaling pathway through a combination of EpCAM promoters in a cis-regulated manner, which promotes HCC cell proliferation in vitro and tumor growth in vivo ( 21 ). In hepatocellular cancer, a signature of immunoautophagy-related lncRNA (IAR-lncRNA) predicts survival ( 27 ). LINC00152 can be used as a biomarker for the differential diagnosis of liver cancer ( 20 ).…”
Section: Function and Mechanisms Of Linc00152 In Human Cancermentioning
confidence: 99%
“…Hu et al (25) reported that interfering with LINC00152 can inhibit proliferation, arrest the cell cycle, and promote apoptosis of hepatocellular cancer cells by regulating the miR-125b-5p/ KIAA1522 axis (25). Wang et al (26) demonstrated that silencing LINC00152 inhibited HCC development by modulating miR-215 to upregulate CDK13 (26). Deng et al (24) found that HBx enhances the expression of LINC00152 and promotes the proliferation and invasion of HCC cells (24).…”
Section: Hepatocellular Cancermentioning
confidence: 99%
“…Meanwhile, some studies have shown that tumor-related lncRNAs could also participate in changing the inherent properties of tumor cells and the expression of immune genes to remodel the tumor immune microenvironment ( Eptaminitaki et al, 2021 ). For example, LINC0187 could affect the prognosis of endometrial cancer, whose high expression may indicate a better prognosis ( Wang Z. et al, 2021 ); the immune-autophagy-related lncRNA signatures including MIR210HG, AC09985.3 and CYTOR as unfavorable prognostic determinants could exhibit a predictive ability in hepatocellular carcinoma (HCC) ( Wang Y. et al, 2021 ); lncRNA including major histocompatibility complex-I (MHC-I) and immunogenicity of tumor (LIMIT) could boost guanylate-binding proteins (GBPs) and MHC-1 to enhance tumor immunogenicity and checkpoint therapy, and the LIMIT-GBP-heat shock factor-1 (HSF1) axis might be a target of cancer immunotherapy ( Li G. et al, 2021 ). However, there are few studies on the association between lncRNAs and BRCA immune microenvironment, and the prognostic value of irlncRNAs in BRCA remains unclear recently.…”
Section: Introductionmentioning
confidence: 99%